2004
DOI: 10.1039/b401145g
|View full text |Cite
|
Sign up to set email alerts
|

Stability improvement of immobilized Candida antarctica lipase B in an organic medium under microwave radiation

Abstract: The influence of microwave heating on the stability of immobilized Candida antarctica lipase B was studied at 100 degrees in an organic medium. The microwave radiation was carried out before enzymatic reaction (storage conditions) or during the enzymatic catalysis (use conditions). In both cases, enzymatic stability was higher under microwave heating than under conventional thermal heating, in strictly identical operating conditions. Furthermore, the gain of enzymatic stability under microwave heating appears … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 12 publications
2
33
0
4
Order By: Relevance
“…[265] Apart from traditional organic and combinatorial synthesis protocols covered in this Review (see Section 2), more recent applications of microwave chemistry include biochemical processes such as a high-speed polymerase chain reaction (PCR), [266] rapid enzyme-mediated protein mapping, [267] and general enzyme-mediated organic transformations (biocatalysis). [268] Furthermore, microwaves have been used in conjunction with electrochemical [269] and photochemical processes, [270] and are also employed in polymer chemistry [271] and material science applications, [272] such as the fabrication and modification of carbon nanotubes or nanowires. [273] So why isn t everybody using microwaves?…”
Section: Methodsmentioning
confidence: 99%
“…[265] Apart from traditional organic and combinatorial synthesis protocols covered in this Review (see Section 2), more recent applications of microwave chemistry include biochemical processes such as a high-speed polymerase chain reaction (PCR), [266] rapid enzyme-mediated protein mapping, [267] and general enzyme-mediated organic transformations (biocatalysis). [268] Furthermore, microwaves have been used in conjunction with electrochemical [269] and photochemical processes, [270] and are also employed in polymer chemistry [271] and material science applications, [272] such as the fabrication and modification of carbon nanotubes or nanowires. [273] So why isn t everybody using microwaves?…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the use of microwaves in lipase-catalyzed reactions has been increasingly studied during the past decade, leading to improvements in conversion, reaction rates, and stereoselectivities (20Á30). Moreover, Rejasse and co-workers demonstrated that the stability of immobilized lipase B from Candida antarctica (CAL B, Novozym 435) in organic media can be enhanced by using microwave dielectric heating rather than conventional thermal heating, thus explaining the enhancements observed in conversion rate (31,32).…”
Section: Research Lettermentioning
confidence: 99%
“…As an example, these effects are used in biocatalysis discipline (Réjasse et al, 2004;2006;Yadav & Borkar, 2009;Souza et al, 2009), DNA hybridization (Edwards, Young, & Deiters, 2009) and the studies that evaluate enzyme stability with the use of microwave irradiation (Rejasse et al, 2007;Young et al, 2008;Izquierdo et al, 2007;Porcelli et al, 1997;La Cara et al, 1999). Recently, Laurence et al (2000), H. Bohr and J. Bohr (2000), Pomerai et al (2003) reported unfolding or structural changes in proteins with microwave irradiations and suggested the inclusion of www.ccsenet.org/ijc…”
Section: Applications In Proteomicsmentioning
confidence: 99%